2019
DOI: 10.1097/qad.0000000000002034
|View full text |Cite
|
Sign up to set email alerts
|

Are European HIV cohort data within EuroCoord representative of the diagnosed HIV population?

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…In this work, we cross-sectionally compared the prevalence of CVD risk factors and the estimated total CVD risk between AMACS and EMENO participants. AMACS includes the majority of the HIV-infected adults living in Greece, and it is representative of the PLHIV on care [35]. EMENO consists of a representative sample of the adult general population living in Ten-year risk of fatal and non-fatal CVD using the Framingham risk score (FRS) was calculated for the individuals >20 years whereas 10-year risk of fatal CVD using the Systematic Coronary Risk Evaluation (SCORE) for the non-diabetic individuals >20 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we cross-sectionally compared the prevalence of CVD risk factors and the estimated total CVD risk between AMACS and EMENO participants. AMACS includes the majority of the HIV-infected adults living in Greece, and it is representative of the PLHIV on care [35]. EMENO consists of a representative sample of the adult general population living in Ten-year risk of fatal and non-fatal CVD using the Framingham risk score (FRS) was calculated for the individuals >20 years whereas 10-year risk of fatal CVD using the Systematic Coronary Risk Evaluation (SCORE) for the non-diabetic individuals >20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported contradictory results when comparing FRS risk in HIV-infected and uninfected individuals, with some reporting higher [44], some similar [22,45] and some even lower [46] risk in HIV-infected. It has been shown that the FRS equations underestimate CVD risk in PLHIV [35,47]. SCORE and FRS have been rarely compared in PLHIV.…”
Section: Hiv-infected Predicted % (95% Ci)mentioning
confidence: 99%
“…The cohorts in our study were large, including national cohorts with near complete coverage of the diagnosed population, and were fairly representative (Supplementary Data 1) [35]. Nevertheless, estimates from cohorts with low coverage should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of being included in the cohort given demographic characteristics was estimated; weights inversely proportional to the inclusion probability were generated. Details of the applied method have been recently published [ 14 ]. Stages 5 and 6 were then re-estimated using the weighted AMACS data and weighted estimates were compared to the unweighted ones.…”
Section: Methodsmentioning
confidence: 99%